Balancing National Security and Human Rights: A Critical Analysis of Nigeria's Anti-Terrorism Laws - Antai, Godswill Owoche; Ekpenisi, Collins; Okonji, Charles Ifeasinachi; Kolo, Eunice Awaji; Okpong, Dennis Edet (NIU Journal of Social Sciences, 2025)
Under the Terrorism (Prevention) Act and other relevant laws, the long-serving war on terror in Nigeria has imposed robust counterterrorism measures. Implementation of the measures resulted in most barebones human right violations that surface serious concerns for checks and balances between national security exigencies and safeguard of liberties. The study is a discourse analysis of the anti-terrorism law of Nigeria scrutinizing its counter-terrorism efficacy and conformance with international human rights standards. Drawing from a doctrinal research approach for the study that critiques prominent concepts surrounding militarization or Islamic counter-terror 'war' and unlawful arbitrary detention and disappearance with political repressions in the name of security research. The scale of human rights violations under Nigeria's counterterrorism regime has been made clear by the Zaria Massacre, IPOB proscription and other human rights reports. Positive examples of balancing security and respecting human rights simultaneously: global international security frameworks such as the US Patriot Act, the UK Counter-Terrorism and Security Act, along with African frameworks such as from South Africa and Kenya through a cross-country review mega-analysis.  The research reveals several shortcomings in the Nigerian counter-terrorism apparatus without adequate legal backing, judicial oversight or practiced accountability mechanisms for security agencies. The study, however, recommends legal and policy reforms to lay an appropriate balance between security and human rights sustainable with robust oversight of the judiciary as well as intelligence-led security practices while not sacrificing international human rights standards and transparency in counter-terrorism keeps. The provisions combined will allow Nigeria to respond with a degree of legitimacy to global security threats while keeping democratic principles and respect for human rights in the cloak of legal counterterrorist policy that national defence is other consideration with fundamental freedoms. Keywords:  National Security, Human Rights, Counterterrorism, Anti-terrorism